Timed-insemination of beef heifers using Cosynch with or without MGA - Wickersham, T.A.; Cochran, R.C.; Grieger, David M. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Our purpose was to determine if feeding melengesterol acetate (MGA) for 1 week in combination with gonadotropin-releasing hormone (GnRH) and prostaglandin-F2" (PGF) would better synchronize heifers for timed artificial insemination. Sixty-nine yearling beef heifers received an injection of GnRH 7 days before receiving an injection of PGF. Half of the heifers were fed MGA between the GnRH and PGF injections (Cosynch+MGA), whereas the remaining heifers were not (Cosynch). All heifers were given a second GnRH injection 2 days after PGF and inseminated at that time. Pregnancy rate for the Cosynch group (43%) was greater (P<0.05) than that for the Cosynch+MGA group (15%). This experiment suggests that short-term feeding (7 days) of MGA in concert with a Cosynch protocol was detrimental to fertility in beef heifers.
Keywords: Beef; Heifers; AI; Synchronization; MGA; GnRh; PGF2a